2009
DOI: 10.2118/09-07-30
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fracture Network System of the Midale Field

Abstract: Enhanced oil recovery from challenging/complex fields requires extensive analysis of reservoir structure and good understanding of the effect of this structure on the dynamics of the process. Naturally fractured reservoirs are good examples of this kind and their fracture network characterization is still a bigchallenge. In this study, we analyzed the fracture network system of a portion of the Midale Field, a naturally fractured carbonate reservoir in the Williston Basin of southeastern Sask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Almost all the cores contain some natural fractures (Beliveau et al 1993); the cores indicate that the fractures are vertical to nearly vertical and open, and the fracture height and spacing range from a few inches to a few feet (Beliveau et al 1993). More recently, detailed information about the formation and fracture characteristics of the Midale field was given by Bogatkov and Babadagli (2009). Beliveau et al (1993) conceptualized the fracture system, as shown in their Figs.…”
Section: Field Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all the cores contain some natural fractures (Beliveau et al 1993); the cores indicate that the fractures are vertical to nearly vertical and open, and the fracture height and spacing range from a few inches to a few feet (Beliveau et al 1993). More recently, detailed information about the formation and fracture characteristics of the Midale field was given by Bogatkov and Babadagli (2009). Beliveau et al (1993) conceptualized the fracture system, as shown in their Figs.…”
Section: Field Examplesmentioning
confidence: 99%
“…We make several observations. First, if the major fractures trend in the northeast/southwest direction with approximately 1-ft fracture spacing, any well must have intersected a number of fractures because they cannot be drilled exactly vertical, and because the average dip calculated for all fracture sets is approximately 80 (Bogatkov and Babadagli 2009). Furthermore, Bunge (2000) reported that fractures intersecting the wellbore were observed from microresistivity imager logs.…”
Section: Field Examplesmentioning
confidence: 99%